Synthesis, Characterization and Antibacterial Activities of Pyrido Dipyrimidines - NANDHA KUMAR, R.; SURESH, T.; MOHAN, P.S. (Asian Journal of Chemistry, 2010)
A one-pot synthesis of pyrido dipyrimidiocs has been achieved from 1,3-diaryl barbituric acid with furfural and aniline. Tlie spectral and analytical data supported the structure of the synthesized compounds and all the compounds were screened for their anubacterial activities against Enterobacteria faecalis and Aeromonas hydrophilla.